Emoticons and Digital Emotions: Effects on Trust, Social Interaction, Emotional Expression, and Emotional Clarity Among Generation Z Students - Daisy Mui Hung Kee; Hao Du; Farah Afiqah Binti Rozman; Farrah Najuwa Binti Sazali; Fatin Alya Syuhadah Binti Fazli (AIBPM Publisher, 2026)
Emoticons have become central to digital communication among Generation Z (Gen Z) university students, serving as visual cues that convey emotional tone and relational intent in text-based interaction. This study examines the effects of emoticon usage on online trust, social interaction, and relationship quality, perceived social support, emotional expression, and emotional clarity among Malaysian university students. A quantitative design was employed, with survey data collected from 155 respondents and analyzed using regression analysis. The results indicate that emoticon usage has significant positive effects on online trust (? = 0.259, p 0.001), social interaction and relationship quality (? = 0.268, p 0.001), perceived social support (? = 0.218, p 0.001), emotional expression (? = 0.249, p 0.001), and emotional clarity (? = 0.616, p 0.001). In addition, emotional clarity is positively associated with online trust (? = 0.508, p 0.001), social interaction and relationship quality (? = 0.595, p 0.001), perceived social support (? = 0.631, p 0.001), and emotional expression (? = 0.664, p 0.001). These findings suggest that emoticons and emotional clarity contribute to emotionally coherent and relationally meaningful digital communication. The study provides practical insights for fostering emotionally responsive interaction in educational and social digital contexts among Gen Z users.